2005
DOI: 10.1097/01.ijg.0000158850.07732.05
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma With the Oculocerebrorenal Syndrome of Lowe

Abstract: A primary X-linked infantile glaucoma is a defining and frequent component of OCRL and is secondary to expression of a primary filtration angle anomaly. Goniotomy was unsuccessful in all (8) operated eyes. The adverse effects of cataract surgery on the filtration angle structures may influence the results of goniotomy surgery by superimposing a secondary aphakic glaucoma component that may explain the need for alternative glaucoma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Biopsies performed past the age of 10 years show interstitial disease of increased severity with secondary glomerulo sclerosis. 6,15 the mechanism of renal failure is not known. norden and colleagues 17 observed that in lowe and similar tubulo pathies, the lowmolecularweight proteins excreted in excess include chemokines and other bioactive proteins, and have speculated that these proteins contribute to interstitial inflammation and fibrosis.…”
Section: Renal Tubular Dysfunction and Renal Failurementioning
confidence: 97%
See 1 more Smart Citation
“…Biopsies performed past the age of 10 years show interstitial disease of increased severity with secondary glomerulo sclerosis. 6,15 the mechanism of renal failure is not known. norden and colleagues 17 observed that in lowe and similar tubulo pathies, the lowmolecularweight proteins excreted in excess include chemokines and other bioactive proteins, and have speculated that these proteins contribute to interstitial inflammation and fibrosis.…”
Section: Renal Tubular Dysfunction and Renal Failurementioning
confidence: 97%
“…5 although goniotomy would be expected to lead to improvement in these patients, such improvements seldom occur, and increased intraocular pressure is rarely relieved by surgical intervention. 6 loss of vision progresses, often to blindness. thus, although glaucoma screening every reviews severe to profound handicap and only about 10% in the range of low to normal intellectual function.…”
Section: Clinical Features and Treatmentmentioning
confidence: 98%
“…At birth, congenital cataract is the most common finding, with other ocular diseases such as glaucoma, corneal cheloid, corneal opacity, nystagmus, and amblyopia also seen 3,8,9 . In the nervous system, neonatal hypotonia and loss or decrease of deep tendon reflexes are frequent initial symptoms with motor development retardation, mental retardation, seizures and growth and development delays also reported 1,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Possibly the early surgical removal of cataract introduces the complexities of aphakic open-angle glaucoma into the clinical picture. 285 This syndrome must be distinguished from the Zellweger (hepatocerebrorenal) syndrome, a lethal peroxisomal biogenesis disorder that causes infantile hypotonia, seizures, and death within the first year. Ophthalmic manifestations include corneal opacification, cataract, glaucoma, pigmentary retinopathy, and optic atrophy.…”
Section: Peter's Anomalymentioning
confidence: 99%